2009
DOI: 10.1007/978-3-642-02710-9_49
|View full text |Cite
|
Sign up to set email alerts
|

Spearcon Performance and Preference for Auditory Menus on a Mobile Phone

Abstract: Abstract. This study investigates the use of spearcons as an auditory cue. It looks simultaneously at both performance and subjective preference of spearcons and text-to-speech (TTS). The study replicated on a mobile phone a previous PC-based study run by Palladino and Walker [1]. Performance results have been very similar to those found in the previous study, supporting the generalizability of spearcon performance from PCs to mobile phones. TTS and spearcons both provided comparable performance improvements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 6 publications
(9 reference statements)
0
7
0
1
Order By: Relevance
“…However, there are many questions remaining to be answered on aesthetics, preference, and annoyance. Recent work has begun to study the subjective improvements to auditory menus from spearcons and other similar enhancements [Walker and Kogan 2009]. Following this line, the present study will show how the user's acceptance level can be changed as a function of preference and annoyance level, despite maintaining a similar level of objective performance.…”
Section: Preference Andmentioning
confidence: 78%
“…However, there are many questions remaining to be answered on aesthetics, preference, and annoyance. Recent work has begun to study the subjective improvements to auditory menus from spearcons and other similar enhancements [Walker and Kogan 2009]. Following this line, the present study will show how the user's acceptance level can be changed as a function of preference and annoyance level, despite maintaining a similar level of objective performance.…”
Section: Preference Andmentioning
confidence: 78%
“…For example, Walker et al [30] showed that spearcons resulted in faster and more accurate performance than other auditory cues for a search task. Spearcons also improved navigation efficiency over auditory menus using only TTS or no sound when combined with visual cues [33][34][35]. Other studies [36,37] have demonstrated that spearcons are as learnable as speech, but auditory icons and earcons were more difficult to learn.…”
Section: Spearcon: Compressed Speech Soundsmentioning
confidence: 99%
“…Si les spearcons de Palladino sont d'un type différent des nôtres (compression logarithmique chez Palladino vs. linéaire), ceux de Dingler sont similaires, la qualité des spearcons que nous avons utilisés ne semble donc pas en cause. Quant aux travaux sur l'acceptabilité des spearcons, la seule étude portant sur ce sujet, celle de Walker [13] n'apporte pas d'élément clair. Enfin, la grande majorité (83%) des sujets n'envisagent pas de se passer du visuel.…”
Section: Discussionunclassified